Case Report: A Variety of Immune-Related Adverse Events Triggered by Immune Checkpoint Inhibitors in a Subject With Malignant Melanoma: Destructive Thyroiditis, Aseptic Meningitis and Isolated ACTH Deficiency - Yukino Katakura; Tomohiko Kimura; Takashi Kusano; Fuminori Tatsumi; Yuichiro Iwamoto; Junpei Sanada; Yoshiro Fushimi; Masashi Shimoda; Kenji Kohara; Shuhei Nakanishi; Kohei Kaku; Tomoatsu Mune; et al. (Frontiers in Endocrinology, 2021)
Recently, immune checkpoint inhibitors have been drawing much attention as cancer immunotherapy, but it has been shown that various immune-related adverse events (irAEs) are induced by immune checkpoint inhibitors in various organs, which has become one of the serious issues at present. A 58-year-old Japanese male with malignant melanoma was treated with nivolumab and/or ipilimumab. During the period of treatment, he suffered from various irAEs. Firstly, about 1 month after starting nivolumab monotherapy, destructive thyroiditis was induced, and so we started replacement therapy with levothyroxine. Secondly, about 1 month after starting nivolumab and ipilimumab combination therapy, aseptic meningitis was induced. We stopped both drugs and started steroid therapy with prednisolone. Finally, about 9 months after restarting nivolumab, isolated adrenocorticotropic hormone (ACTH) deficiency was induced, and so we started replacement therapy with hydrocortisone. Taken together, we should bear in mind the possibility of a variety of irAEs when we use immune checkpoint inhibitors.